Melbourne - Forbes, Tony (Sydney : Edition Habit Press, 2005)
Poster showing pictorial map of Melbourne with icons such as Albert Park, St. Kilda Pier and Melbourne Cricket Ground highlighted.
"Limited edition 500."
Caption title.
Keywords: Posters, Australian; Melbourne (Vic.) -- Posters; Australia -- Posters; Australian